A estudiar se aprende : metodología de estudio : sesión por sesión - García-Huidobro, Cecilia; Gutiérrez G., María Cristina; Condemarín G., Eliana (Ediciones IC, 2010)
With technical, educational and neuropsychological foundations, a study methodology devised by three psychologists with vast experience is presented. With the application of the proposed method that is included in the book, students will have the possibility of increasing their academic performance, learning more in less time. A first theoretical part analyzes the factors that intervene in school learning. In the practical part, strategies are proposed to understand, summarize, take notes, make diagrams and improve the logistical, affective and social aspects involved in learning. The authors are educational psychologists from the Pontifical Catholic University of Chile.